MATHEMATICAL METHODS FOR DECISION-MAKING : MATHEMATICAL METHODS FOR DECISION-MAKING - Dimanova , Donika (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The report will set out a systematic introduction to the mathematical methods that facilitate decision-making in many areas of human activity. Especially important are these methods in solving problems in the management and decision-making in emergency situations. The formation of strategic and tactical decisions, the governing body must take into account the multiple and conflicting considerations of which to seek the most effective option.